Assignments of FIR laser lines from optically pumped (CH3OH)-C-13 - Moraes, João Carlos Silos [UNESP]; Carelli, G.; Moretti, A.; Moruzzi, G.; Strumia, F. (Academic Press Inc. Jnl-comp Subscriptions, 1996)
We have revisited the assignments of the far-infrared laser lines emitted by (CH3OH)-C-13 by comparing the laser systems to a high resolution Fourier transform absorption spectrum of (CH3OH)-C-13. The absorption spectrum was analyzed by means of the ''Ritz'' program, which calculates the energy level values directly from the Rydberg-Ritz combination principle. We report new assignments for 11 FIR laser transitions, 17 frequency predictions for new possible laser lines, and we confirm 11 previous assignments. (C) 1996 Academic Press, Inc.